The Vagus Nerve and Spleen: Influence on White Adipose Mass and Histology of Obese and Non-obese Rats - Kuchler, Joice Cristina; Siqueira, Bruna Schumaker; Ceglarek, Vanessa Marieli; Chasko, Fernanda Vigilato; Moura, Isllany Carvalho; Sczepanhak, Bruna Fatima; Vettorazzi, Jean Franciesco; Balbo, Sandra Lucinei; Grassiolli, Sabrina (Frontiers in Physiology, 2021)
The vagus nerve (VN) and spleen represent a complex interface between neural and immunological functions, affecting both energy metabolism and white adipose tissue (WAT) content. Here, we evaluated whether vagal and splenic axis participates in WAT mass regulation in obese and non-obese male Wistar rats. High doses of monosodium glutamate (M; 4g/Kg) were administered during the neonatal period to induce hypothalamic lesion and obesity (M-Obese rats). Non-obese or Control (CTL) rats received equimolar saline. At 60 days of life, M-Obese and CTL rats were randomly distributed into experimental subgroups according to the following surgical procedures: sham; subdiaphragmatic vagotomy (SV); splenectomy (SPL) and SV+SPL (n= 11 rats/group). At 150 days of life and after 12 hours of fasting, rats were euthanized, blood was collected and the plasma levels of glucose, triglycerides, cholesterol, insulin, and IL10 were analyzed. The visceral and subcutaneous WAT depots were excised, weighed and histologically evaluated for number and size of adipocytes as well as IL10 protein expression. M-Obese rats showed higher adiposity, hyperinsulinemia, hypertriglyceridemia, and insulin resistance when compared to CTL groups (p<0.05). In CTL and M-Obese rats, SV reduced body weight gain and triglycerides levels, diminishing adipocyte size without changes in IL10 expression in WAT (p<0.05). The SV procedure resulted in high IL10 plasma levels in CTL rats, but not in the M-Obese group. The splenectomy prevented the SV anti-adiposity effects, as well as blocked the elevation of IL10 levels in plasma of CTL rats. In contrast, neither SV nor SPL surgeries modified the plasma levels of IL10 and IL10 protein expression in WAT from M-Obese rats. In conclusion, vagotomy promotes body weight and adiposity reduction, elevating IL10 plasma levels in non-obese animals, in a spleen-dependent manner. Under hypothalamic obesity conditions, VN ablation also reduces body weight gain and adiposity, improving insulin sensitivity without changes in IL10 protein expression in WAT or IL10 plasma levels, in a spleen-independent manner. Our findings indicate that the vagal-spleen axis influence the WAT mass in a health state, while this mechanism seems to be disturbed in hypothalamic obese animals.